Investigation of non-genetic factors affecting haematological traits in dorper sheep - Makgopa, Ledimo Faith (My University, 2024)
Haematological parameters may be affected by several internal and external factors making their interpretation more challenging. Non-genetic factors are known to have an influence on haematological parameters of sheep, therefore it is important to investigate the influence of non-genetic factors on haematological parameters, which could be useful in determining health, physiological changes, metabolic status, as well as disease diagnosis and prognosis. This study was aimed at establishing the effect of non-genetic factors such as sex, age, physiological status, and body condition score on haematological parameters of Dorper sheep at the University of Limpopo Experimental farm, South Africa. A total of thirty (n = 30) sheep (19 females and 11 males) were used as experimental animals. The blood samples were collected from each sheep via jugular venipuncture using 5 ml syringes and 21-gauge needles. The samples were analysed at Ampath Laboratories in Pretoria, South Africa, using Sysmex analyser (XE-2100). The haematological parameters including red blood cell count (RBC), white blood cell count (WBC), haemoglobin count (Hb), Normoblast count (NB), Platelet count (Plt), Haematocrit (Hct), Eosinophil count (Eos), monocyte count(Mn), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), neutrophil count (NEU), absolute neutrophil count (ANC), absolute monocyte count (AMC), absolute lymphocyte count (ALC), Lymphocyte count (LYM), red blood cell distribution width (RDW), basophils (BASO) and absolute eosinophil count (AEC) were analysed. Non-genetic factors collected were body condition score (1 to 5 scale), physiological status (pregnant and non-pregnant), age (1 to 6 years) and sex (male and female). Pearson’s correlation was used to determine the relationship between haematological parameters. General Linear Model procedure (GLM) was used to determine the effect of sex, age, body condition score and physiological parameters on haematological parameters. Correlation results indicated that RBC was positively high correlated (p < 0.01) with Hct, WBC, ALC, Eos, AEC, and negatively high correlated (p < 0.01) with MCV, Mn, and NB. However, RBC had no significant correlation (p > 0.05) with MCHC, RWD, NEU, ANC, AMC, BASO, ABC, and Plt. The results showed that sex had an influence (p < 0.05) on Hb and RWD, and high significant influence (p < 0.01) on LYM and NB. The findings indicated that physiological status had an effect (p < 0.05) on RDW. The findings also showed that body condition score and age had no significant effect (p > 0.05) on all the studied haematological parameters. The results suggest that sex and physiological status influenced haematological parameters of Dorper sheep. It was concluded that sex and physiological status should be considered when examining the health, nutritional, metabolic status to improve the productivity and management practiced of Dorper sheep.
Thesis (M. Sc. Agriculture (Animal Production)) -- University of Limpopo, 2024
Keywords: Haematological parameters; Dorper sheep; Sex; Age; Body condition score; Physiological status; Dorper sheep; Blood -- Examination; Epigenetics